Desain Bahan Ajar Berorientasi Pemecahan Masalah untuk Mencapai Higher Order Thinking Skills (HOTS) Peserta Didik di Kelas X SMA/MA - Melia Aula Adami; Amali Putra; Yurnetti Yurnetti (Universitas Negeri Padang, 2018)
This research is aimed to design problem-oriented teaching materials to improving students’ Higher Order Thinking Skills (HOTS). Skills of HOTS include analyze (C4), evaluate (C5), and creativity (C6) which can be trained with problem-oriented learning. This type of research is research and development (R & D) with ADDIE’s model that is limited until third stages are :1) analysis, 2) design, 3) development. The subjects of this researchare five lecturers of Physics Faculty of Mathematics and Natural Sciences as a validator, three teachers of Physics in SMAN 16 Padang as practitioners, and one class of X MIA students in SMAN 16 Padang for product test. Instruments used consisted of the validity and practicality of teaching materials that have been prepared. The result of this research is the result of valid and practical teaching materials, with the percentage of validity is 82,74% are on very valid criteria, practically according to the teacher with the percentage 88,61% are on very practical criteria, and practically of students’ re sponse with percentage 87, 24% are on very practical criteria.